Early release of methane and quicker degradation of bioplastics using activated sludge - Chethan Kumar Mukunda; Kavya Manjula Gurubasavaiah; Syeda Hajira Banu (The Holistic Approach to Environment)
Environmental hazards caused by fossil-based plastics are spread through every ecosystem of the biosphere. As an alternative, biodegradable plastics are environmentally friendly and sustainable. Composting biodegradable plastics is a big challenge. Microorganisms in anaerobic conditions convert biodegradable plastics into methane, carbon dioxide, water, hydrogen sulphide, ammonia, and hydrogen. In the present study, locally procured sugarcane bagasse plates, cornstarch-based shopping bags and bamboo starch-based spoons of size < 1 cm2 (cut pieces) were anaerobically digested using activated sludge under mesophilic conditions to evaluate the production of biogas (liquid displacement) and methane (liquid replacement). The structural changes of biodegradable plastics were analysed using Fourier transform infrared spectroscopy - attenuated total reflectance (FTIR-ATR) and scanning electron microscopy (SEM). Peak shifts and increase in the intensities of several functional groups were observed in FTIR-ATR for all three biodegradable plastics. Changes in colour, texture and surface porosity were observed. The methane curve showed that the sugarcane bagasse plates were easily degraded. Biogas and methane were immediately produced. The cornstarch-based shopping bag is degraded after a “lag phase”, indicating hydrolysis as the rate-limiting step in anaerobic digestion. The bamboo starch-based spoon showed inhibition in the initial phase for up to 14 days which reduced the production of methane and then the methane release occurred.